Facebook – et nyt brugersegment for Ordbog over Dansk Talesprog - Abildgaard, Louise Hallstrøm; Glargaard, Amalie; Hansen, Carsten (Nordiske Studier i Leksikografi, 2018)
Ordbog over Dansk Talesprog (ODT) – a Dictionary of Spoken Danish – is a project under the LANCHART Centre at the University of Copenhagen. Following ODT’s online launch in October 2014 which received a lot of attention in Danish media, the ODT team decided to create a Facebook (FB) page for the project as well. This article describes the process of developing an explicit strategy for integrating the FB page and its audience into the work of the team, and how to differentiate between and manage two different platforms, namely the website and the FB page. Early on, the scope was to generate more traffic to the ODT website. However, due to FB having such a vast user group and being a different type of medium altogether, it became necessary to broaden that initial scope. Analyzing Facebook statistics, developing a strategy for publishing updates and particularly a decision to modify the very academic language of the website to better suit the FB format, all proved fruitful in generating FB traffic, if not traffic directly to the website. Thus, FB has become a separate channel of distribution, parallel to that of the website, but – at least potentially – reaching a much wider audience.